Angular‐Resolved Magnetometry Beyond Triclinic Crystals: Out‐of‐Equilibrium Studies of Cp*ErCOT Single‐Molecule Magnet1. Issue 41 (3rd September 2013) - Boulon, Marie‐Emmanuelle; Cucinotta, Giuseppe; Liu, Shan‐Shan; Jiang, Shang‐Da; Ungur, Liviu; Chibotaru, Liviu F.; Gao, Song; Sessoli, Roberta
Abstract Angular‐resolved single‐crystal magnetometry is a key tool to characterise lanthanide‐based materials with low symmetry, for which conjectures based on idealised geometries can be totally misleading. Unfortunately the technique is strictly successful only for triclinic structures, thus reducing significantly its application. By collecting out‐of‐equilibrium magnetisation data the technique was extended to the orthorhombic organometallic Cp*ErCOT single‐molecule magnet (SMM), thus allowing for the first time the reconstruction of the molecular anisotropy tensor notwithstanding the two molecular orientations in the crystal lattice. The results, flanked by state‐of‐the‐art ab initio calculations, confirmed the expected orientation of the molecular easy axis of magnetisation and thus validated the synthetic strategy based on organometallic complexes of a single lanthanide ion.